The operating characteristics of intercity public van service in Lampung, Indonesia. - Arintono, Sulistyo (University of South Florida, 2010)
The business of providing pickup and delivery service for intercity passengers flourishes in Indonesia. In Lampung Province, it is available to popular destinations, including Jakarta, Palembang, and Bakauheni. To date, there is no detailed information regarding operating characteristics, highlighting the importance of this research for future reference. The data for analysis were collected through a series of field surveys on service frequency and passenger and driver interviews conducted at the ferry terminal of Bakauheni. Results of the analysis suggest that there are too many vehicles operating on the Bandar Lampung-Bakauheni route. The implications are that the total number of trips, the number of passengers carried, and crew income per vehicle per day are limited. The vehicle queuing and dispatching system needs to be improved to prevent passengers from waiting too long. The conclusion is that this business is profitable only if there is a good operating arrangement.